Digitalisasi Pemasaran Produk UMKM: Inovasi, Branding, dan Ekspansi Pasar - Nur Muniroh; Fajar Mahardika; Ratih, Ratih; Widya Pratiwi (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a vital sector in Indonesia’s economy; however, they still face significant challenges in effectively marketing their products in the digital era. The main issues encountered include a lack of product innovation, weak branding strategies, and limited market expansion through digital platforms. MSME products often do not follow market trends and lack unique selling points, while the brands built tend to be unappealing and inconsistent both visually and narratively. On the other hand, the utilization of digital technology to reach wider markets remains limited due to low digital literacy and the absence of effective marketing strategies. This program aims to provide a comprehensive solution through training and mentoring in digital marketing, focusing on innovative product development, brand identity strengthening, and the use of social media, e-commerce, and SEO. It is expected that this initiative will enhance MSMEs' competitiveness, expand their market reach, and establish a more adaptive and sustainable business ecosystem amid technological advancement